A pilot study to compare passive lumbar spine re-positioning error in those with chronic low back pain with healthy volunteers. (July 2014) - Clark, C. J.; Docherty, S.; Osborne, N.; Khattab, A.
Abstract : Study design: Cross-sectional laboratory study. Objective: To compare the difference in passive re-positioning accuracy in the frontal plane, as a measure of lumbar kinaesthesis, between participants with chronic non-specific low back pain (CNSLBP) and healthy volunteers. Background: Evidence suggests that spinal kinaesthesis impacting on spinal stability might be compromised in those with CNSLBP. It is suggested that in those with CNSLBP, there may be changes in ligamentous patho-physiology which lead to altered kinaesthetic perception. Methods: Fourteen female participants, representing two groups, took part in the study. Participants in group one ( n = 7) were those with CNSLBP (mean age 47.1 ± 15.41) and participants in group two ( n = 7) were healthy volunteers (mean age 45.6 ± 10.63). There were no significant differences between the groups with regards to age, education, height, weight, hip, and waist circumference and all were right handed. Passive lumbar re-positioning accuracy was measured in the frontal plane using a motorized plinth with the Zebris ® ultrasound-based motion analyser and the target positions were 10° left and right lumbar side flexion and neutral. Results: The mean reporting error for the neutral position for participants with CNSLBP vs. healthy volunteers was <2.4° and <2.2° on both occasions ( P > 0.05), respectively. The mean reporting error in left-side flexion for participants with CNSLBP vs. healthy volunteers was <1.5° and <2.0° on both occasions ( P < 0.01; P < 0.05). The mean reporting error in right-side flexion for participants with CNSLBP vs. healthy volunteers was <2.1° and <1.1° on both occasions ( P > 0.05). Conclusion: There was a statistically significant difference in passive re-positioning accuracy to the left side only between participants with CNSLBP and healthy volunteers. This may represent an important finding in relation to structures that provide sensory information and the integration of that information in those with CNSLBP.